Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1162/jocn_a_01326
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory Correlates of Control over Working Memory Gating and Updating: An EEG Study Using the Reference-back Paradigm

Abstract: Optimal working memory (WM) functioning depends on a control mechanism that balances between maintenance and updating by closing or opening the gate to WM, respectively. Here, we examined the neural oscillation correlates of WM updating and of the control processes involved in gating. The reference-back paradigm was employed to manipulate gate opening, gate closing, and updating independently and examine how the control functions involved in these processes are mapped to oscillatory EEG activity. The results e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 81 publications
7
31
0
Order By: Relevance
“…Third, an fMRI study showed BG activation only when switching from comparison to reference trials (Nir-Cohen, Kessler, & Egner, 2019), suggesting this particular condition indeed involves the gating mechanism in BG (Chatham & Badre, 2015;Frank et al, 2001;Hazy et al, 2006;O'Reilly, 2006). Lastly, an EEG study revealed that transitions from reference to comparison trials elicited increased midfrontal theta power (Rac-Lubashevsky & Kessler, 2018), consistent with a need for distractorresistant maintenance of WM. In summary, the referenceback paradigm is well-suited to disentangle component processes of WM.…”
Section: Introductionmentioning
confidence: 96%
“…Third, an fMRI study showed BG activation only when switching from comparison to reference trials (Nir-Cohen, Kessler, & Egner, 2019), suggesting this particular condition indeed involves the gating mechanism in BG (Chatham & Badre, 2015;Frank et al, 2001;Hazy et al, 2006;O'Reilly, 2006). Lastly, an EEG study revealed that transitions from reference to comparison trials elicited increased midfrontal theta power (Rac-Lubashevsky & Kessler, 2018), consistent with a need for distractorresistant maintenance of WM. In summary, the referenceback paradigm is well-suited to disentangle component processes of WM.…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, incongruent conclusions generate more information to be updated in the WM, producing larger anterior delta power than congruent conclusions; T− needs more WM to be updated than S−, producing larger anterior delta power; and T+ needs less WM to be updated than S+, producing less anterior delta power. These speculations are supported by Rac-Lubashevsky and Kessler (2018), who suggested that WM updating is related to an increase in anterior delta power.…”
Section: Discussionmentioning
confidence: 66%
“…In phase-locked power, the premise monotonicity effect during semantic category-based induction was revealed by delta power in the 100–350 ms time window. In the cognitive domain, delta oscillations are related to signal detection, decision-making, attention, inhibition, or working memory (Spironelli and Angrilli, 2010; Putman, 2011; Leszczyński et al, 2015; Rac-Lubashevsky and Kessler, 2018; reviews, Knyazev, 2012; Harmony, 2013; Güntekin and Başar, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, meditators did show a higher proportion of participants with fronto-midline theta peaks above the 1/f aperiodic activity. Theta activity has been related to attentional function, particularly cognitive control (Cavanagh & Frank, 2014; Rac-Lubashevsky & Kessler, 2018; Sauseng et al, 2010; Sauseng et al, 2007), and previous research has indicated that meditators show increases in theta activity (Kerr et al, 2013; Lagopoulos et al, 2009; Tang et al, 2009). As such, it may be that meditation practice enabled a higher proportion of the meditation group to generate theta oscillations to maintain attention on the task during the WM delay period.…”
Section: Discussionmentioning
confidence: 99%